Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Self-Healing Cs3Bi2Br3I6 Perovskite Wafers for X-Ray Detection - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marcus; These, Albert; Matt, Gebhard; Brabec, Christoph; Tedde, Sandro F.; et al. (Advanced Functional Materials, 2021)
Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3Bi2Br3I6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer-based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X-ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self-healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X-ray detectors; however, the aged device outperforms all others. Thus, self-healing acts in Cs3Bi2Br3I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bismuth halides; lead-free perovskites; photoconductors; self-healing; X-ray detection

Six metal cations in one double perovskite: exploring complexity of chloride elpasolites by high-throughput experimentation - Stroyuk, Oleksandr; Raievska, Oleksandra; Daum, Manuel; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
A high-throughput screening of lead-free double chloride perovskites Cs2MIMIIICl6 is performed combining combinatorial robot-assisted synthesis with accelerated structural and spectral characterizations. The screening encompasses about 350 elpasolite compounds with broad variations of the MIII site, including combinations of two (Bi + In, Bi + Sb, and In + Sb) and three cations (In + Bi + Sb and Fe + Bi + In). The robot-assisted open-environment synthesis protocol allows the double perovskites with these MIII combinations and Ag+/Na+-occupied MI site to be produced using a general routine in the form of single-phase microcrystalline solid solutions with reliably controlled composition. The high-throughput screening revealed a series of non-additive effects arising from the combination of multiple cations on the MIII site, including a “volcano”-shaped dependence of the photoluminescence quantum yield of Cs2(Ag,Na)(Bi,In)Cl6 elpasolites on Ag/Na and Bi/In ratio and band-bowing effects in the compositional dependences of the bandgaps of perovskites with Bi + Sb, In + Bi + Sb, and Fe + Bi + In combinations. In the latter case, the accelerated screening resulted in the double chloride perovskites with an unusually low indirect bandgap of 1.64 eV.
CRIS-Team Scopus Importer:2024-06-14